Far from the tree [videorecording (DVD)] - Kingsley, Jason, 1974-; Solomon, Andrew, 1963- (Sundance Selects, 2019)
"FAR FROM THE TREE follows families meeting extraordinary challenges through love, empathy, and understanding. This life-affirming documentary encourages us to cherish loved ones for all they are, not who they might have been. Based on Andrew Solomon's award-winning, critically acclaimed, New York Times bestselling non-fiction book "Far From the Tree: Parents, Children and the Search for Identity."--Container.